Immune Status Against Hepatitis B in Patients After Allogeneic Hematopoietic Cell Transplantation—Factors Affecting Early and Long-Lasting Maintenance of Protective Anti-HBs Titers - Piekarska, Agnieszka; Wisniewski, Piotr; Lewandowski, Krzysztof; Gil, Lidia; Trzonkowski, Piotr; Bieniaszewska, Maria; Zaucha, Jan Maciej (Frontiers in Immunology, 2020)
The immunization of allogeneic hematopoietic cell transplantation (HCT) recipients against vaccine-preventable diseases is a part of posttransplantation guidelines. We conducted a prospective study to assess clinical and immunological parameters that would determine the response and long-term maintenance of protective antibody titers upon the hepatitis B virus (HBV) vaccination after HCT. The investigated variables included: vaccination of the HCT recipients and their donors prior to HCT, chronic graft versus host disease (cGVHD) and the timing of post-HCT vaccination, and B- and T-cell subtype status. Forty-two patients were immunized with three or more doses of recombinant hepatitis B surface antigen (rHBsAg) administered according to the individualized schedule of 0-1-2-6-(12) months. After vaccination, seroconversion was achieved in the whole group. The vaccinees were categorized according to the antibody (Ab) titers as weak (WRs; 28.7%), good (GRs; 38%) or very good responders (VGRs; 3.3%). In multivariate logistic regression, severe cGVHD (OR= 15.5), and preceding donor immunization (OR= 0.13) were independent predictors of a weak response to vaccination. A prior belonging to the WR group impaired the durability of protection (OR= 0.17) at a median follow-up of 11.5 years. Patients with severe cGVHD showed a trend toward lower median Ab titers, although they required a higher rate of booster vaccine doses. All VGRs had CD4+ cells > 0.2 x 106/L. There was a lower mean rate of CD4+IL2+ lymphocytes in WRs. Vaccination demonstrated the immunomodulatory effect on B-cell and T-cell subsets and a Th1/Th2 cytokine profile, while shifts depended on a history of severe cGVHD and the type of vaccine responder. To conclude, vaccination of HCT donors against HBV allows a better response to vaccination in the respective HCT recipients. Double doses of rHBsAg should be considered in patients with cGVHD and in those not immunized before HCT. A dedicated intensified vaccination schedule should be administered to WRs.